Transformational Leadership Communication in Building Digital Culture within Higher Education Institutions - Novika Ayu Triany; Muhammad Akbar; Alem Febri Sonni (Borong Newinera Publisher, 2026)
This study examines the role of transformational leadership communication in building digital culture within higher education institutions. As universities face increasing pressure to adapt to rapid technological advancements, digital transformation extends beyond the adoption of technology and requires a fundamental shift in organizational culture, values, and practices. This research adopts a qualitative approach using an exploratory multiple case study design to capture in-depth insights into leadership communication processes. Data were collected through semi-structured interviews, document analysis, and observations involving academic leaders and faculty members engaged in institutional transformation initiatives. The findings reveal that visionary communication plays a crucial role in articulating a shared direction and aligning stakeholders, while dialogic communication fosters trust through open, participatory engagement. In addition, strategic communication helps manage resistance by addressing concerns, reframing change, and promoting acceptance. Communication also functions as a driver of organizational learning by enabling knowledge sharing, reflection, and continuous adaptation. The study highlights that effective leadership communication is not limited to information dissemination but involves meaning-making, relationship-building, and cultural integration. The integration of transformational and adaptive communication practices emerges as a key factor in sustaining digital transformation and embedding digital values into institutional practices. This research contributes to the literature by emphasizing the centrality of communication in leadership and digital culture development, particularly within the context of higher education in Indonesia.